Role of remittance in GDP growth of Nepal - Pant, Chet Raj; Bashyal, Sarita; Pant, Keshab Raj (AMC Journal (Dhangadhi), 2023)
This article deals with the analysis of role of remittance in gross domestic production (GDP) growth of Nepal where compression is made with import and export as well. Considering the GDP as dependent variable and the remittance, import and export as the independent variables, the analysis is performed based on the secondary sources of data published by Nepal Rastra Bank (NRB) in last 10 years (2012-2022) and other data available in literatures using the linear models under multiple regressions. The role of remittance has been seen significant effect on the GDP. For the mentioned study period, average GDP growth is 4.49% however it was in decreased by 2.36% in the 2019/20. The possible reason of the decrease will be due to the outburst of COVID- 19 pandemic worldwide. At the same time, average remittance inflow was 11.09% where it was negative 0.48% in 2020/21. In addition, the flow of remittance is rising, which boosts economic expansion and import volume. Imports make up two thirds of all trade, with exports accounting for the remaining below one third. Economic growth is positively impacted by both imports and exports. When the effects of exports and imports are combined, exports have a negative impact on Nepal's economic growth. Exports have no beneficial effect on economic growth, despite favorable effects from imports.